Adolescent Weight and Depressive Symptoms For Whom is Weight a Burden? - Frisco, Michelle L (Social science quarterly, 2009)
OBJECTIVE: Adolescent weight and depressive symptoms are serious population health concerns in their own right and as they relate to each other. This study asks whether relationships between weight and depressive symptoms vary by sex and race/ethnicity because both shape experiences of weight and psychological distress